Comparison of Software-Defined Radios for Performance Evaluation of High Precision Clocks - Andrich, Carsten; Bauer, Julia; Ihlow, Alexander; Beuster, Niklas; Galdo, Giovanni Del (IEEE International Symposium on Precision Clock Synchronization for Measurement, Control, and Communication, ISPCS, 2018)
For precision clock analysis in terms of sine (10 MHz) and pulse per second (1 PPS) reference signals, usually the dual-mixer time difference (DMTD) method and the time interval counter (TIC) were used. This paper addresses the application of adequate software-defined radio (SDR) platforms, instead. As hardware, the Universal Software Radio Peripheral (USRP) N210 and X310 by Ettus Research LLC are compared with respect to the attainable measurement precision. Implementing a digital down-conversion (DDC) with subsequent phase comparison for the 10 MHz signals and a Schmitt-trigger with subsequent two-stage interpolation for detecting the edges of the 1 PPS signals, we pay special attention to the specifics of the two platforms and demonstrate how to exploit modern x86 processor architectures. As results, we evaluate the remaining measurement uncertainty in terms of the the Allan deviation and the time interval error, which stems inherently from the investigated SDR platforms in connection with the proposed DSP algorithms.
CRIS-Team Scopus Importer:2025-11-10
Keywords: 1 pulse per second (1 PPS); 10 MHz; Clocks; Computerized instrumentation; Digital signal processing (DSP); Measurement techniques; Phase measurement; Software-defined radio (SDR); Time measurement